Staphylococcus capitis and NRCS-A clone: the story of an unrecognized pathogen in neonatal intensive care units. (September 2019) - Laurent, F.; Butin, M.
Abstract: Background: In neonatal intensive care units (NICUs), nosocomial late-onset sepsis (LOS), mostly due to coagulase negative staphylococci, constitute a major cause of death or impairment. Staphylococcus capitis, usually considered as a poorly virulent species, has been reported as a cause of LOS. Objectives: To review data regarding S. capitis neonatal LOS and the features of isolates involved. Sources: PubMed was searched up to August 2018 to retrieve studies on the topic; the keywords used were 'S. capitis', 'neonate', 'neonatal ICU', 'bloodstream infection' and 'late onset sepsis'. Content: Published data highlight the worldwide endemicity of a single S. capitis clone, named NRCS-A, specifically involved in LOS. NRCS-A harbours a multidrug resistance profile (including resistance to the usual first-line antibiotics used in NICUs). It is also able to adapt under vancomycin selective pressure that could confer an advantage for its implantation and dissemination in NICUs where this selective pressure is high. Moreover, a severe morbidity has been observed in NRCS-A-related LOS. The NICU environment, and especially incubators, constitute reservoirs of NRCS-A from which it could diffuse inside the setting. Finally, the virulome and resistome of S. capitis NRCS-A contain many genes potentially implicated in its specific epidemiology and pathophysiology, including the gene nsr that may be involved in its fitness and implantation in neonatal gut flora. Implications: S. capitis must be considered as a true pathogen in neonates. The decreased susceptibility to vancomycin may be involved in failure of vancomycin therapy. Further studies are needed to better manage its diffusion inside each NICU but also worldwide.